Dampak Pengembangan Karir dan Kepemimpinan terhadap Kinerja Karyawan dengan Loyalitas Kerja sebagai Variabel Intervening - Ahmad Marzuki; Slamet Ahmadi; Deni Fakhrudin (J-MAS (Jurnal Manajemen dan Sains), 2022)
This research includes quantitative research conducted at PT American Standards Indonesia. This study aims to determine whether or not career development and leadership impact employee performance through work loyalty as an intervening variable. This study, 100 respondents were used as samples, calculated using the Slovin formula from 406 populations at a margin of error of 5%. It collected data using a Likert scale and an assessment using a Questionnaire. The data analysis method used by the researcher is a statistical test using SPSS version 23 using analytical techniques, a classical assumption test, a path test, a coefficient of determination, and hypothesis testing. The study yielded seven main findings according to the proposed hypothesis; namely, the first path test in the study concluded that there was a significant impact between 1) career development on employee performance; 2) leadership on employee performance. The results of the second path test concluded that there was a significant impact between 3) loyalty to employee performance, 4) career development to work loyalty, 5) leadership to work loyalty, 6) career development through work loyalty as an intervening variable, and 7) leadership through work loyalty to employee performance. The results of this study suggest a number of steps that can be taken to improve performance in the context of providing promotions for employees who perform well, the role of leaders who can arouse the passion of employees and, obey and work loyally to improve employee performance.